TINDAK TUTUR PERCAKAPAN GURU DAN SISWA DALAM PEMBELAJARAN OLAHRAGA DI SDN PETINGGEN - Firdaus, Fahmi (JURNAL SKRIPTA, 2024)
Speech act events are frequently utilized to learn specific knowledge; they are differentiated by the presence of speakers and speech partners. The purpose of this study is to explain and describe (1) the speech actions employed in teacher and student dialogues in sports learning at SDN Petinggen, as well as (2) the meaning/intention behind the communication between the teacher and students in sports learning. The qualitative research approach is used in this study. Data is collected through observation and recording procedures. For analysis, the flow approach was applied. This study's findings may be summarized as follows: (1) how instructors and students utilize locutionary, illocutionary, and perlocutionary speech actions in learning; (2) the goal of the teacher and student dialogue, such as educating, motivating, clarifying, reinforcing, amusing, and finishing. The instructor does speech acts in order to develop good communication with pupils using various tactics and speaking strategies that take into account the context of formal or casual circumstances. Thus, the instructor student conversation in sports learning involves both direct and indirect speaking activities.